Intra-abdominal sepsis: new definitions and current clinical standards - Hecker, Andreas; Reuß, Christopher; Schmoch, Thomas; Weigand, Markus A. (Langenbeck's archives of surgery, 2019)
The abdomen is the second most common source of sepsis and is associated with unacceptably high morbidity and mortality. Recently, the essential definitions of sepsis and septic shock were updated (Third International Consensus Definitions for Sepsis and Septic Shock, Sepsis-3) and modified. The purpose of this review is to provide an overview of the changes introduced by Sepsis-3 and the current state of the art regarding the treatment of abdominal sepsis.